ANALISIS PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, SARANA DAN PRASARANA PENDIDIKAN TERHADAP KINERJA GURU DI SMPN 36 SURABAYA - Dr. Drs. Sugito, M.M. (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
Analyzing the influence of principal leadership, educational facilities and infrastructure on teacher performance is very important because it can help improve the quality of education in an educational institution, namely improving teacher performance, increasing teacher motivation, improving the quality of education, determining the right policies and strategies, and strengthening the management of educational institutions.... This study aims to analyze the effect of principal leadership, educational facilities and infrastructure on teacher performance at SMPN 36 Surabaya. The research method used is a survey method using a questionnaire to collect data from respondents consisting of teachers at SMPN 36 Surabaya. The collected data were analyzed using simple linear regression analysis technique. The results showed that the principal's leadership, educational facilities, and educational infrastructure significantly affect teacher performance at SMPN 36 Surabaya. Principal leadership has a positive and significant effect on teacher performance, while educational facilities and educational infrastructure also have a positive and significant effect on teacher performance. Thus, it can be concluded that principal leadership, educational facilities, and educational infrastructure are important factors in improving teacher performance at SMPN 36 Surabaya.